حركات الجسد في رواية (شجرة البؤس) لطه حسين دراسة دلالية سياقية - علي, گەشە عبدالله; أحمد, دلير عبدالله (Sulaimani Journal for Humanities, 2022)
This research titled (body movements in the novel of The Tree of Misery by Taha Hussein - a semantic contextual study) aims at studying body movements as messages that carry different emotional and psychological connotations stemming from within the human being. It can sometimes dispense with the spoken language, and even be more expressive and the effect on the recipient is stronger than communication in words. Words and structures are no longer the only means of communication in the context of interacting with each other. Rather, there is the silent language represented by the body and the gestures of the body members and their movements in different situations and events. Body language plays its effective functional role in managing the communication process and accurately conveying thoughts, feelings and emotions to the recipient. This study started from the importance of physical movement in the communicative context, the eloquence of discourse, and the need to pay attention to its role in the literature text. We chose the novel (The Tree of Misery) by Taha Hussein to monitor the impact of body language in it by subjecting its models to analysis in search of their contextual implications. Taha Hussein, The Dean of Arabic Literature was keen to diversify the ways of conveying meanings to the recipient and producing connotations in his narrative discourse in addition to spoken language. He employed body language and tried to describe live images that reflect circumstances and situations that expressed the different feelings and emotions experienced by the characters.